Perancangan Company Profile Berbasis Website Pada Desa Tanjung Kemala Kecamatan Baturaja Timur - M Rezy; Pujianto Pujianto; Abdul Rahman (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2024)
This study aims to create a website-based Company Profile of Tanjung Kemala Village, East Baturaja District, to facilitate the people of Tanjung Kemala Village. Providing better village profile openness to the community regarding village facilities and village advantages, the company profile website will be an easily accessible source of information for all parties who want to find out more about the village and provide community services Tanjung Kemala Village, East Baturaja District. In designing and building a company profile website in Tanjung Kemala village using WDLC methods, namely Planning, Analysis, Website Design and Development, Testing, Website Implementation and Maintenance. Website creation using codeigniter framework and database using Mysql. This research resulted in a website company profile of village services The proposed web-based can maximize services at the Tanjung Kemala Village Office as planned and provide quick information about health, social education and village profiles. By having a modern and informative company profile website, Tanjung Kemala Village can increase the value of promotion and professionalism in the eyes of the community.